The Noggin Cove Formation: a Middle Ordovician back-arc basin deposit in northeastern Newfoundland - Johnston, D.; Williams, H.; Currie, K. (Atlantic Geology, 1994)
The Noggin Cove Formation is the largest volcanic unit of the eastern Exploits Subzone. It is approximately 1 km thick and consists mainly of stratified mafic volcaniclastic rocks with subordinate pillowed basalt and Mack shale. Stratigraphtc relationships and regional correlations indicate a Middle Ordovician age. The Carmanvillc Melange and the distinctive Woody Island formation, with coticule layers and olistostromes, occur along the northern margin of the Noggin Cove Forma tion, and the formation is faulted against siltstone and shale of the Davidsvilte Group along its southern margin. The Noggin Cove Formation underwent three periods of deformation: (1) Dj, early recumbent Fj folding; (2) T>2> northeast-trending tight to isoclinal F2 folding with pervasive axial planar cleavage (S2); and (3) D3, open east-plunging F3 folding of the regional S2 cleavage. Regional greenschist facies metamorphism was locally followed by contact mctamor-phism related to intrusion of the Siluro-Devonian Frederickton, Rocky Bay and Aspen Cove plutons. Facies distribution, ubiquitous vesicular clasts, and the volume of monomictic volcaniclastic rocks imply that the Nog gin Cove Formation is an erosional marine volcaniclastic apron built up to the south of a shallow marine to subaerial evolving volcanic source. Back-arc geochemical affinities, coupled with lithology and stratigraphy, indicate a back-arc basin paleotectonic setting.